Seeing-from: imagined viewing and the role of hideouts in theatre - Moura, Vítor (2014)
The objective of this paper is to assess in what ways the dramaturgic device of hideouts is capable of prompting the spectator into an awareness of what it is to be watching and / or what it is to sense being stared at. At the same time we want to consider the implications of this rather paradoxical situation of assuming that someone is invisible when everything else in theatre is designed for visualization. Also, we want to test the hypothesis that theatrical hidden characters constitute a device akin to cinematic subjective shots, leading to the question of how the experience of watching a hidden character on stage alters the theatre spectator’s imagining and visualizing.